The Impact of the Use of Massage on the Reflective Points and Approximate Exercises of Running and Standing Phase according to some Bio-kinematical Variables for Front Jumps of Skill Hands on the Platform Jumping on the Arising National Team Technical Gym - Abdul Slam Abdul Razzaq, Zinah; Abdul Hussein Waheeb, Suad (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to prepare massage exercises and the use of the reflective points to improve approximate jogging and stage the advancement of bio-kinematical running variables to approximate the advancement of skill, hands, leap forward, platform jumping, and sample search. The research also aims to identify the impact of the use of the reflective exercise massage to improve running points in the approximate phase and the advancement of jump skill hands headlights on the platform jumping according to some biokinematical variables. Prepared exercises and massages contributed to the reflective points in time (10m) and affected the walking distance and the seriousness of the glove and speed (4 steps) and had a positive impact on the time to seek macroeconomic policies on the glove in accordance with the conclusions reached by the researchers, who recommend that attention be recruited for 1,872 scientific papers dealing with the modern methods of hospitalization and benefit from the results of this study and its application within other training curricula of other actors.